Adherence reporting in randomized controlled trials. (April 2014) - Zhang, Ze; Peluso, Michael J; Gross, Cary P; Viscoli, Catherine M; Kernan, Walter N
Background: Treatment adherence may influence the therapeutic effect that is observed in a randomized controlled trial (RCT). Adherence may also be an indicator of research quality and treatment acceptance by participants. Despite the importance of adherence in RCT research, little is known about current practices for its measurement and reporting. Purpose: The objective of this study was to determine and evaluate adherence measurement and reporting practices in RCTs involving oral pharmacologic interventions published in high impact factor journals. Methods: We conducted a systematic review of RCTs involving oral pharmacotherapy published during 2010 in 10 high-impact general medicine and subspecialty journals. Two investigators independently abstracted data regarding trial characteristics, adherence monitoring, and adherence reporting. Differences were reconciled in conference. Descriptive statistics were calculated, statistical comparisons were made using chi-square analysis, and associations assessed using Spearman's rank correlation coefficient. Results: Of 111 RCT manuscripts included in the sample, 51 (45.9%) reported study-drug adherence among participants. Studies that reported adherence results were more likely to report negative findings (i.e., no significant treatment effect in a superiority trial, non-equivalence in an equivalence trial) (p = 0.032). The most common method for adherence monitoring was pill count-back on returned bottles. Among the studies that reported adherence, the median adherence was 88.4% (range: 48%−100%), and trials with longer follow-up time reported lower adherence (r = −0.45; p = 0.0015). A minority of the 51 studies described a strategy for calculating adherence that accounted for participants who were lost to follow-up (11/51 studies; 21.6%), discontinued the study medication temporarily (6/51 studies; 11.8%), or discontinued the study drug permanently (1/51 study; 2%). Limitations: This study is limited by the inclusion of a small set of journals with the highest impact factors in specific fields of clinical medicine, including general medicine. Although the analysis pertains to studies published in 2010, no new guidelines in the field since the last Consolidated Standards of Reporting Trials (CONSORT) statement have been issued that would be expected to change practices for adherence monitoring, analysis, and reporting. Conclusions: Adherence measurement methodology and results are underreported in published RCTs. In the minority of RCTs that provided adherence information, there was substantial heterogeneity in how adherence was defined, analyzed, and reported. Improved reporting of adherence may enhance the interpretation of study quality and results.